Pharmacokinetics‐Based Design of Subcutaneous Controlled Release Systems for Biologics - Abigail K. Grosskopf; Antonio A. Ginart; Phillip Spinosa; Vittal Shivva (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Protein therapeutics have emerged as an exceedingly promising treatment modality in recent times but are predominantly given as intravenous administration. Transitioning to subcutaneous (SC) administration of these therapies could significantly enhance patient convenience by enabling at‐home administration, thereby potentially reducing the overall cost of treatment. Approaches that enable sustained delivery of subcutaneously administered biologics offer further advantages in terms of less frequent dosing and better patient compliance. Controlled release technologies, such as hydrogels and subcutaneous implantable technologies, present exciting solutions by enabling the gradual release of biologics from the delivery system. Despite their substantial potential, significant hurdles remain in appropriately applying and integrating these technologies with the ongoing development of complex biologic‐based therapies. We evaluate the potential impact of subcutaneously delivered controlled release systems on the downstream pharmacokinetics (PK) of several FDA‐approved biologics by employing rigorous mathematical analysis and predictive PK simulations. By leveraging linear time‐invariant (LTI) systems theory, we provide a robust framework for understanding and optimizing the release dynamics of these technologies. We demonstrate simple quantitative metrics and approaches that can inform the design and implementation of controlled release technologies. The findings highlight key opportunity areas to reduce dosing frequency, stabilize concentration profiles, and synergize the codelivery of biologics, calling for collaboration between drug delivery and PK scientists to create the most convenient, optimized, and effective precision therapies.